A Study on Optimizing an Effective Online Platform to Address Plastic Waste Management in Sri Lanka - Weerasinghe, H. S. R. A.; Alwis, D. C. D.; Ginorajh, R.; Harischandra, G. D. S. (International Journal of Advanced Science Computing and Engineering, 2023)
Plastic waste is a severe environmental problem with far-reaching effects on the environment, human health, and the economy. Therefore, sustainable methods for managing plastic waste are essential to protecting the environment and guaranteeing a cleaner, healthier future for the next generations. Unfortunately, Sri Lanka is currently grappling with a serious plastic waste management problem, with plastic waste volumes increasing rapidly over the years. However, the issue extends beyond environmental concerns, permeating social and economic spheres. Rapid urbanization, population growth, and low stakeholder awareness of the problem are some of the contributing factors. This requires introducing an effective and efficient system incorporating technology to improve solutions. The proliferation of technology has significantly impacted the global marketplace, resulting in an expanding customer and vendor base. This development has triggered a departure from traditional buying and selling methods, as digitalized platforms offer an efficient approach to securing ideal consumer products. Although countless online fashion platforms exist, many lack a commitment to environmental sustainability. This paper discusses a web-based application designed to accumulate PET (Plastic Polyethylene Terephthalate) bottles, recycle them, and convert them into clothing products. Web-based PET bottle collection is a new innovative feature that addresses this prominent environmental concern. The process generates various polyester threads by separating and reprocessing plastic waste, which is subsequently used to create desired clothes. The ultimate objective of the application is to establish an online clothing store that efficiently manages the plastic waste in Sri Lanka.